Development and validation of bioanalytical method for amlodipine in human plasma with optimised extraction method using Design of Experiment (DOE) - Helal Uddin, A.B.M.; Alaama, Mohammed; Mohamad, Huda Jamilah; Amirudin, N. S. (2015)
Amlodipine is antihypertensive drug belonging to calcium antagonist group. This study aims to apply experimental design for the optimization of extraction method of amlodipine from human plasma for higher and constant recovery. A chromatographic method involving HPLC (High Performance Liquid Chromatography) with DAD (Diode Array Detector) was developed and validated for the determination of Amlodipine in human plasma with cetirizine as internal standard. Sample preparation for the extraction of Amlodipine and Cetirizine (Internal Standard) from plasma was optimised using DOE (Design of Experiment). Three different parameters namely solvent type, solvent volume and pH were monitored at different level for the optimisation of sample preparation that would produce best recovery of the analytes. For this purpose, three level full factorial design, which involves 27 experiments, was conducted. The recovery of amlodipine was determined using the developed and pre validated HPLC-DAD method with an Agilent 1100 HPLC system. Chromatographic separation of the analytes was obtained using phenomenix (150X4.5 mm, 5 um) C18 column. The mobile phase consists of 35:65 v/v of ACN: 0.3% triethylamine with pH adjusted at 3 using phosphoric acid. Detection of analyte was conducted using a diod array detector at 237 nm wavelength. Design Expert 8.0 software was used to interpret all data obtained from the optimisation study. For the parameters solvent and solvent volume “acetonitrile” and “1 ml” was found to be the optimum values required to extract amlodipine and internal standard while pH had no effect on the optimum recovery. The recovery of amlodipine and internal standard was 80-88% and 85-99% respectively.